The Impact of Postoperative Tumor Burden on Patients With Brain Metastases - Aftahy, Amir Kaywan; Barz, Melanie; Lange, Nicole; Baumgart, Lea; Thunstedt, Cem; Eller, Mario Antonio; Wiestler, Benedikt; Bernhardt, Denise; Combs, Stephanie E.; Jost, Philipp J.; Delbridge, Claire; Liesche-Starnecker, Friederike; et al. (Frontiers in Oncology, 2022)
Background Brain metastases were considered to be well-defined lesions, but recent research points to infiltrating behavior. Impact of postoperative residual tumor burden (RTB) and extent of resection are still not defined enough. Patients and Methods Adult patients with surgery of brain metastases between April 2007 and January 2020 were analyzed. Early postoperative MRI (<72 h) was used to segment RTB. Survival analysis was performed and cutoff values for RTB were revealed. Separate (subgroup) analyses regarding postoperative radiotherapy, age, and histopathological entities were performed. Results A total of 704 patients were included. Complete cytoreduction was achieved in 487/704 (69.2%) patients, median preoperative tumor burden was 12.4 cm3 (IQR 5.2–25.8 cm3), median RTB was 0.14 cm3 (IQR 0.0–2.05 cm3), and median postoperative tumor volume of the targeted BM was 0.0 cm3 (IQR 0.0–0.1 cm3). Median overall survival was 6 months (IQR 2–18). In multivariate analysis, preoperative KPSS (HR 0.981982, 95% CI, 0.9761–0.9873, p < 0.001), age (HR 1.012363; 95% CI, 1.0043–1.0205, p = 0.0026), and preoperative (HR 1.004906; 95% CI, 1.0003–1.0095, p = 0.00362) and postoperative tumor burden (HR 1.017983; 95% CI; 1.0058–1.0303, p = 0.0036) were significant. Maximally selected log rank statistics showed a significant cutoff for RTB of 1.78 cm3 (p = 0.0022) for all and 0.28 cm3 (p = 0.0047) for targeted metastasis and cutoff for the age of 67 years (p < 0.001). (Stereotactic) Radiotherapy had a significant impact on survival (p < 0.001). Conclusions RTB is a strong predictor for survival. Maximal cytoreduction, as confirmed by postoperative MRI, should be achieved whenever possible, regardless of type of postoperative radiotherapy.